Convergence of Information and Communication Technology (ICT) sectors in the East African Community (EAC): Challenges for the current legislative and regulatory frameworks and lessons from the European Union experience - Joseph Kariuki Nyaga (International Telecommunications Society (ITS), 2011)
The East African Community (EAC)'s Information and Communication Technology (ICT) sector has been confronted with the convergence phenomenon. This is a concept that describes the trend of blurring boundaries between the traditionally distinct ICT sectors, namely: Information Technology (IT), broadcasting and telecommunications. This is significant for the EAC since the driving force behind this convergence phenomenon is that of efficiency. It necessitates the need to rethink the current legislative and regulatory frameworks in the ICT sector in order to cope with this phenomenon. The need to address this is pertinent since adapting to legislative and regulatory frameworks that are fully converged will expand access to ICT, stimulate economic growth, technological advancement, and also faster integration process of the EAC. Therefore this paper aims to demonstrate the following: Implications and challenges of this trend for the EAC legislative and regulatory frameworks; the need for a common legislative and regulatory framework that is fully converged. It therefore focuses on the inadequacies of the existing legislative and regulatory frameworks and reveals the lacunae in the present frameworks and how they fail to adequately address convergence phenomenon. The paper recommends effective, workable and consistent proposals on how to address the inadequacies. This brings awareness and deepens the understanding of the regulatory convergence issues to the ICT stakeholders in the region and the challenges of convergence on the existing frameworks. This will contribute to better legislative and regulatory frameworks in the EAC ICT market. It will therefore enable the region to enjoy the benefits of convergence and minimise instances of inefficiency in regulation of these converged ICT markets.
Keywords: 330; East African Community (EAC); Legislative and Regulatory Harmonization; Convergence; Information and Communication Technology (ICT); Regulation